The Emerald handbook of work, workplaces and disruptive issues in HRM - Holland, Peter 1963-; Bartram, Timothy; Garavan, Thomas N.; Grant, Kirsteen, active 2022 (Emerald Publishing Limited, 2022)
Technology advancement and the widespread impacts of the COVID-19 pandemic have had a major impact on both the contours and terrain of work, employment, and the management of people. Understanding these complex developments requires fresh perspectives on the nature and context of the management of people and human resources. The expanding fourth industrial revolution has been underpinned by new technological platforms and AI, as well as new worker motivations, making essential that researchers seek to explore the field of HRM in a new way. The Emerald Handbook of Work, Workplaces, and Disruptive Issues in HRM reflects these complex changes in the way work, employment and people currently are and will continue to be managed across the globe. Considering these changes, a multidisciplinary range of voices illustrate just how fundamental recent developments will be in reshaping work and employment as in any previous revolution. The Handbook is structured into three sections: Human Resource Management, Human Resource Development, and Emerging Issues, each exploring key themes and the emergence of ground-breaking new perspectives. These themes are central issues for debate and discussion in the workplaces across the globe and the work presents innovative and provocative assessments of changes and challenges in rapidly evolving local and global environments.
Keywords: Personnel management.; Business & Economics -- Human Resources & Personnel Management.; Personnel & human resources management.; elektronické knihy; electronic books